Investigations of the charge symmetry breaking reaction dd → απ0 with the WASA-at-COSY experiment - Źurek M. (EPJ Web of Conferences, 2014)
The charge symmetry breaking reaction dd → 4Heπ0 has been measured with the WASA-at-COSY experimental setup at a beam momentum of pd = 1.2 GeV/c (Q = 60 MeV). For the ﬁrst time a signal for this reaction has been observed at an excess energy well above threshold. The determined preliminary total cross section is σtotprel = (120±20stat.) pb.